Dengue epidemic in Tamaulipas in the year 2005: From the stomatology analysis - Turrubiates-Ortiz, Mónica Esmeralda (Universidad Autónoma de Tamaulipas, 2009)
The dengue fever is an infectious disease of viral etiology, it is transmitted primarily by the Aedes Aegypti mosquito, which clinically presents itself with the classic dengue, with hemorrhage and the shock syndrome one, also in various manifestations of the disease. The purpose of this article is to report the frequency of the oral manifestations of the classic dengue and the hemorrhage fever ones when the disease spread in 2005 in Tamaulipas. For that a sample of 715 patients were taken to the Children Hospital of Tamaulipas with a dengue fever clinical symptom, this information was obtained from the report and the clinical file. It was found that during the epidemic period 6,901 cases where registered all throughout the state, and that 30.5% of the cases where less than 19 years old. During this time the Children’s Hospital in Tamaulipas received 715 cases, 593(83%) of these patients had the classic dengue fever and the other 122 (17%) was hemorrhagic dengue. The alteration in the taste buds was the major clinical proof of the virus. The gingivitis and petechia in the oral mucus where the more frequent cases of hemorrhagic dengue in these cases. The oral proofs of dengue are more frequent in the hemorrhage form, this is why there is an alarm because o the clinical evolution of the disease. It is important that all cases diagnosed with dengue fever should check themselves very meticulously to explore that oral cavity